A comparison of the effects of micronutrient seed priming and soil fertilization on the mineral nutrition of chickpea (Cicer arietinum), lentil (Lens culinaris), rice (Oryza sativa) and wheat (Triticum aestivum) in Nepal. - Johnson, S.E.; Lauren, J.G.; Welch, R.M.; Duxbury, J.M. (Cambridge University Press, 2005)
Soil deficiencies of zinc (Zn) and boron (B) limit crop production in Nepal. Improving the micronutrient status of plants would increase yield and increase micronutrient content of the seeds, leading to better nutrition of the progeny crop and to improved human micronutrient nutrition. The primary micronutrient problem in grain legumes is B deficiency, while in rice (Oryza sativa), Zn deficiency is more important, and wheat (Triticum aestivum) suffers from both deficiencies. A series of field experiments was carried out over two seasons to compare soil fertilization and micronutrient seed priming as methods of improving Zn and B nutrition of each crop. Micronutrient treatments were evaluated for their effect on grain yield and grain micronutrient content. Soil B fertilization increased B content of the grain of lentil (Lens culinaris), chickpea (Cicer arietinum), and wheat by a factor of two to five, while increasing the yield of chickpea only. Soil fertilization with Zn had no effect on yield of any crop, but resulted in a small increase in Zn in wheat grain. Sowing micronutrient-primed seeds had no effect on yield or micronutrient content of the progeny seeds in most cases. During the first season, the primed chickpea seeds failed to emerge at either site, causing complete yield loss, but this negative effect was not observed in the second season with similar priming treatments at nearby sites, and no effect of priming on yield was observed with any other crop in either season.